2007
DOI: 10.1590/s0103-64402007000300016
|View full text |Cite
|
Sign up to set email alerts
|

Jarabak 's cephalometric analysis of Brazilian black patients

Abstract: The treatment of skeletal disharmonies presents better results when performed during the growth period. The physical changes that occur in every individual express growth, which is ruled by genetic, general and environmental factors. In order to identify such disharmonies and hence concentrate the clinical actions during treatment and influence facial growth, cephalometrics appears as a useful a diagnostic tool for identifying facial growth patterns or growth direction. Jarabak's cephalometric analysis is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
0
17
1
2
Order By: Relevance
“…The Caucasians had significantly higher (p<0.001) mean value compared to Nepalese. In contrast, the mean value of sum of angles was not statistically significant among Brazilian black subjects when compared to Caucasians 21 .…”
Section: Discussioncontrasting
confidence: 60%
“…The Caucasians had significantly higher (p<0.001) mean value compared to Nepalese. In contrast, the mean value of sum of angles was not statistically significant among Brazilian black subjects when compared to Caucasians 21 .…”
Section: Discussioncontrasting
confidence: 60%
“…A report by Kuramae et al26 found that cephalometric measurements calculated for black Brazilian patients were similar to Jarabak's standards, except for S-N mean value for female patients, which was significantly lower than the established Jarabak's standard. The application of Björk and Jarabak analysis in all mentioned studies reinforces its relevance in the current context of orthodontic diagnosis, but no reports highlight findings on an adult population.…”
Section: Discussionmentioning
confidence: 81%
“…A large number of cephalometric methods and analyses have been suggested in the orthodontic literature [1] since the introduction of cephalometry in 1931 [2,3]. Cephalometrics is also important in the field of anthropology for understanding of the ethnic dentofacial characteristics of various populations [4,5]. Because of the variation in craniofacial features in different populations, for appropriate application of any cephalometric analysis, it should preferably be used with norms derived from a population similar to that of the actual orthodontic patients with regard to ethnic group, gender and age.…”
Section: Introductionmentioning
confidence: 99%